2022
DOI: 10.1111/1751-7915.13994
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of nasal cavities by Staphylococcus epidermidis mitigates SARS‐CoV‐2 nucleocapsid phosphoprotein‐induced interleukin (IL)‐6 in the lung

Abstract: Summary Infection by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can trigger excessive interleukin (IL)‐6 signalling, leading to a myriad of biological effects including a cytokine storm that contributes to multiple organ failure in severe coronavirus disease 2019 (COVID‐19). Using a mouse model, we demonstrated that nasal inoculation of nucleocapsid phosphoprotein (NPP) of SARS‐CoV‐2 increased IL‐6 content in bronchoalveolar lavage fluid (BALF). Nasal administration of liquid coco‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Pretreatment with a riboflavin kinase inhibitor (i.e., roseoflavin) can reduce the electricity production in Gram-positive bacteria [29]. In this study, we showed that a 24 h pretreatment of L. plantarum MA with roseoflavin significantly reduced the concentration Pretreatment with a riboflavin kinase inhibitor (i.e., roseoflavin) can reduce the electricity production in Gram-positive bacteria [29].…”
Section: Effect Of Fmn On Electricity Generation Of L Plantarum Mamentioning
confidence: 58%
See 2 more Smart Citations
“…Pretreatment with a riboflavin kinase inhibitor (i.e., roseoflavin) can reduce the electricity production in Gram-positive bacteria [29]. In this study, we showed that a 24 h pretreatment of L. plantarum MA with roseoflavin significantly reduced the concentration Pretreatment with a riboflavin kinase inhibitor (i.e., roseoflavin) can reduce the electricity production in Gram-positive bacteria [29].…”
Section: Effect Of Fmn On Electricity Generation Of L Plantarum Mamentioning
confidence: 58%
“…Pretreatment with a riboflavin kinase inhibitor (i.e., roseoflavin) can reduce the electricity production in Gram-positive bacteria [ 29 ]. In this study, we showed that a 24 h pretreatment of L. plantarum MA with roseoflavin significantly reduced the concentration of FMN by approximately 12 folds ( Figure 3 b) while also decreasing electricity production ( Figure 3 c), suggesting that the bioelectrical activity of L. plantarum MA was mediated through the FMN-based EET system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic‐based experimental treatments for other nasal persistent conditions such as rhinitis are under investigation (Sarfraz et al., 2024 ), and the airway probiotic activity of other bacterial components of the human nasal microbiome is being explored. This is the case for nasal Staphylococcus epidermidis , whose protective role against influenza and SARS‐CoV‐2 viral infections has been shown, as it fermentates carbon‐rich molecules yielding short‐chain fatty acids and electricity, which have anti‐inflammatory properties and influence bacterial nasal colonization, respectively (Kao et al., 2022 ). In this context, direct topical probiotic use in the respiratory tract could also be considered as a targeted treatment option for chronic lung disease patients.…”
Section: The Oral–lung Axis Intertwines the Oral And Airway Microbiom...mentioning
confidence: 99%
“…SARS-CoV-2 N-protein also up-regulates the expression of tissue factor and intracellular adhesion molecule 1, markers involved in vascular coagulation and inflammation, and glucose transporter 4, a diabetic marker [ 27 ]. Lastly, complement activation and the activation of signaling pathways through Toll-like receptor 2 might be involved in increasing levels of IL-6 in the lungs of mice inoculated nasally with SARS-CoV-2 N-protein and inducing acute lung injury in mice administrated intratracheally with SARS-CoV-2 N-protein [ 26 , 28 ]. Indeed, the lung injury is associated with NF-κB p65 phosphorylation.…”
Section: Induced Inflammation By Sars-cov-2 N-proteinmentioning
confidence: 99%